Comparison of reflectance confocal microscopy and line‐field optical coherence tomography for the identification of keratinocyte skin tumours. Issue 1 (24th November 2022) - Cinotti, Elisa; Bertello, Martina; Cartocci, Alessandra; Fiorani, Diletta; Tognetti, Linda; Solmi, Valentina; Cappilli, Simone; Peris, Ketty; Perrot, Jean Luc; Suppa, Mariano; Del Marmol, Veronique; Rubegni, Pietro
Abstract: Background: Reflectance confocal microscopy (RCM) and line‐field confocal optical coherence tomography (LC‐OCT) are non‐invasive imaging devices that can help in the clinical diagnosis of actinic keratosis (AK) and cutaneous squamous cell carcinoma (SCC). No studies are available on the comparison between these two technologies for the identification of the different features of keratinocyte skin tumours. Objectives: To compare RCM and LC‐OCT findings in AK and SCC. Methods: A retrospective multicenter study was conducted. Tumours were imaged with RCM and LC‐OCT devices before surgery, and the diagnosis was confirmed by histological examinations. LC‐OCT and RCM criteria for AK/SCC were identified, and their presence/absence was evaluated in all study lesions. Gwet AC1 concordance index was calculated to compare RCM and LC‐OCT. Results: We included 52 patients with 33 AKs and 19 SCCs. Irregular epidermis was visible in most tumours and with a good degree of agreement between RCM and LC‐OCT (Gwet's AC1 0.74). Parakeratosis, dyskeratotic keratinocytes and both linear dilated and glomerular vessels were better visible at LC‐OCT than RCM ( p < 0.001). Erosion/ulceration was identified with both methods in more than half of the cases with a good degree of agreement (Gwet AC1 0.62). Conclusions: Our results suggest that both LC‐OCT and hand‐held RCM can help clinicians in the identification of AK and SCC, providing an in vivo and non‐invasive identification of an irregular epidermis. LC‐OCT proved to be more effective in identifying parakeratosis, dyskeratotic keratinocytes and vessels in this series.